2016
DOI: 10.1111/mmi.13485
|View full text |Cite
|
Sign up to set email alerts
|

UAP56 is a conserved crucial component of a divergent mRNA export pathway in Toxoplasma gondii

Abstract: SummaryNucleo‐cytoplasmic RNA export is an essential post‐transcriptional step to control gene expression in eukaryotic cells and is poorly understood in apicomplexan parasites. With the exception of UAP56, a component of TREX (Transcription Export) complex, other components of mRNA export machinery are not well conserved in divergent supergroups. Here, we use Toxoplasma gondii as a model system to functionally characterize TgUAP56 and its potential interaction factors. We demonstrate that TgUAP56 is crucial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 78 publications
(129 reference statements)
0
22
0
Order By: Relevance
“…For transient gene disruption, each gene-specific gRNA (sequences in Table S4) vector, synthesised by GenScript using backbone vector pU6-SAG1gRNA-DHFR (Serpeloni et al, 2016), was co-transfected with the CAS9-FLAG expressing vector (pU6-universal) (Sidik et al, 2016).…”
Section: Plasmid Constructmentioning
confidence: 99%
“…For transient gene disruption, each gene-specific gRNA (sequences in Table S4) vector, synthesised by GenScript using backbone vector pU6-SAG1gRNA-DHFR (Serpeloni et al, 2016), was co-transfected with the CAS9-FLAG expressing vector (pU6-universal) (Sidik et al, 2016).…”
Section: Plasmid Constructmentioning
confidence: 99%
“…Perhaps investigations of the nuclear transport machineries in other divergent eukaryotes will help answer this question. Indeed, a recent study has shown that mRNA export pathways in Apicomplexa also appears to be divergent 86 ; in addition, so far investigators have been unable to identify any Mex67 orthologs in Toxoplasma gondii, indicating that this organism may be even more divergent Figure 3. Evolution of the NPC.…”
Section: Tms and Alps: Multiple Ways To Tether A Leviathanmentioning
confidence: 99%
“…86 In fact, very little is known about mRNA processing and export in most protists. Thus our study highlights and reinforces the need to sample and study a broad distribution of eukaryotic taxa to gain insight into evolutionary origins of function and mechanism at the nuclear envelope -as well as of course in many other cellular processes.…”
Section: Tms and Alps: Multiple Ways To Tether A Leviathanmentioning
confidence: 99%
“…For transient gene disruption, each gene specific gRNA (sequences in Table S2) vector, synthesised by GenScript using backbone vector pU6-SAG1gRNA-DHFR (Serpeloni et al, 2016), was co-transfected with the CAS9-FLAG expressing vector (pU6-universal) (Sidik et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…CRISPR/Cas9 transient expression - Parasites transiently co-expressing CAS9-FLAG expressing vector (pU6-universal) (Sidik et al, 2016) and gene specific sgRNA containing vector (Serpeloni et al, 2016), for genes TGME49_214790 / 263680 and 226280 , were fixed 24 hours post-transfection. The CAS9-FLAG and mitochondria were visualised by immunofluorescence as described above.…”
Section: Methodsmentioning
confidence: 99%